Parapropus jasminkoi sp. n., a new leptodirine beetle (Coleoptera: Leiodidae, Cholevinae) from Bosnia and Herzegovina - Polak, Slavko (Acta entomologica slovenica (Ljubljana), 2015)
New species of leptodirine beetle Parapropus jasminkoi sp.n. is described from Otlovića pećina on Čemernica planina in Northern Bosnia. Identification key to similar small species that share short pronotum, P. brevicollis Müller, P. nonveilleri Müller and P. vitorogensis Ćurčić S., Pešić & Ćurčić B.P.M. is provided.
Keywords: beetles; Bosna in Hercegovina; Bosnia and Herzegovina; Cholevinae; Coleoptera; hrošči; Leiodidae; Leptodirini; new species; nova vrsta; Parapropus; troglobiont